Effects of electron doping on the stability of the metal hydride NaH. (1st March 2017) - Olea-Amezcua, M A; Rivas-Silva, J F; de la Peña-Seaman, O; Heid, R; Bohnen, K P
Abstract: Alkali and alkali-earth metal hydrides have high volumetric and gravimetric hydrogen densities, but due to their high thermodynamic stability, they possess high dehydrogenation temperatures which may be reduced by transforming these compounds into less stable states/configurations. We present a systematic computational study of the electron doping effects on the stability of the alkali metal hydride NaH substituted with Mg, using the self-consistent version of the virtual crystal approximation to model the alloy Na1− x Mg x H. The phonon dispersions were studied paying special attention to the crystal stability and the correlations with the electronic structure taking into account the zero point energy contribution. We found that substitution of Na by Mg in the hydride invokes a reduction of the frequencies, leading to dynamical instabilities for Mg content of 25%. The microscopic origin of these instabilities could be related to the formation of ellipsoidal Fermi surfaces centered at the L point due to the metallization of the hydride by the Mg substitution. Applying the quasiharmonic approximation, thermodynamic properties like heat capacities, vibrational entropies and vibrational free energies as a function of temperature at zero pressure are obtained. These properties determine an upper temperature for the thermodynamic stability of the hydride, which decreases from 600 K for NaH to 300 K at 20% Mg concentration. This significant reduction of the stability range indicates that dehydrogenation could be favoured by electron doping of NaH.